PSYCHOLOGICAL RESOURCES OF THE FAMILY IN THE CONDITIONS OF WAR (Psychology Travelogs, 2024)
The article examines the psychological resource of the family, which contributes to emotional support and psychological protection of family members. It was found that the concept of "psychological resources of the family" reflects the personal attributes and abilities of people connected by family ties with spouses (blood relatives, several generations of relatives), which help each other adapt to stressful situations, overcome them and restore personal comfort. Such personal properties and abilities of a family member are: wisdom and knowledge (flexibility of thinking, ability to overcome difficulties and resistance of circumstances, understanding of family roles that contribute to the realization of emotional function), empathy (sympathy, desire to care for family and friends, sensitivity in relationships), authority (deserves the respect and trust of relatives and close people), communicativeness (listens carefully, understands and delicately convinces family members).It was found that the most important models of behavior of family members for the implementation of the emotional function of the family in the conditions of war include the following family roles: protector (protector), friend, leader, motivator (muse), optimist, adviser, listener, interlocutor, counselor, humorist. Practical recommendations have been developed for family members on the implementation of emotional function in war conditions. They will help family members to realize their psychological resource and effective behavior patterns for providing emotional support, psychological protection and restoration of emotional comfort of family members.
Keywords: family; psychological resources; conditions of war; emotional function; family roles